The interactive Surveying Instructor (ISI) for teaching Optical-Mechanical Instrument Reading in Surveying Engineering - Garbanzo León, Jaime (2018)
The Interactive Surveying Instructor (ISI) is an extension of the work developed by Garbanzo and Lara (2018), who created a web 2.0 app for teaching leveling in surveying engineering. Two improvements were made to enhance the user experience and include surveying equipment that is important in the initial stages of engineering training: developing a new web interface using Bootstrap 4.0.0 and a module for optical mechanical theodolite. Often, these students have problems practicing in the field because they need a peer to assist them with equipment; this situation can hinder their learning. ISI was developed using PHP, MySQL, and JavaScript, and it is a lightweight web application designed to simulate the equipment readings. Furthermore, the readings made by students are stored in a database for analysis. ISI is operational but is still not suitable for mobile screens. Adapting it for mobile devices is the next step in this project.